Les biblioteques dels carmelites descalços de la província de Sant Josep de Catalunya (1586-1835). - GRAS CASANOVAS, MERCÈ (Scripta, 2016)
This paper aims to provide an initial overview of the libraries of the Catalan Discalced Carmelites. Teresa of Jesus, the founder of the Order, based on his own reading experience, gave some initial rules regarding monastic libraries, which would be developed in the future by the authorities of the Order, as regards both their contents and their care and maintenance. The different types of monastic libraries were often enriched by donations from devotees, both secular and ecclesiastical, which established a series of conditions on their legacies. Finally, we present the assessments made by scholars about some of these libraries, as well as some information of their status and destiny on occasion of the confiscation of properties of the religious (Desamortització)